The effect of perceived organizational support on organizational citizenship behavior mediated by employee engagement and employee development in F&B employees in Indonesia - Anggraeni, Sufi; Malini, Helma; Saputra, Pramana (Junal Ilmu Manajemen, 2025)
The food and beverage industry, both nationally and internationally, has been an essential factor in Indonesia's economic development and contributes significantly to GDP and employment. With increasing globalization and rapidly changing consumer preferences, business owners and entities operating within this sector will face more challenges. One of the challenges facing the F&B industry today is the effort to increase productivity. In this case, Organizational Citizenship Behavior is essential to increase employee productivity and performance. However, F&B industry employees still have low OCB levels. Perceived organizational support is needed to optimize the formation of OCB behavior. In addition, Employee Engagement and Employee Development are also considered to help improve Organizational Citizenship Behavior. In this instance, the study intends to investigate how perceived organizational support influences organizational citizenship behavior and ascertain how employee engagement and development function as mediators. This study employs a quantitative methodology using the Partial Least Squares in the Smart PLS version 4.0 application and the Structural Equation Modeling (SEM) PLS research method. With a sample of 180 respondents, the study's population consisted of all F&B workers in Indonesia. According to the survey, employee engagement mediates between perceived organizational support and organizational citizenship behavior. However, employee development does not show this impact. These results give human resource managers in Indonesia's F&B industry an important direction on boosting employee engagement and organizational support to promote constructive and pleasant workplace behaviors.